1993
DOI: 10.1021/ic00067a024
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen atom transfer between cis-coordinated nitrite and nitrosyl ligands: The case of the CpCr(NO)2(NO2)/CpCr(NO)2(ONO) linkage isomers

Abstract: CpCr(N0)2(N02) exists as a mixture of the nitro and nitrito linkage isomers, with the nitrito isomer predominating in both solution and the solid state (Cp = rj5-C5H5). The Cr-N02 ** Cr-ONO equilibrium is markedly solvent and temperature dependent: in CDC13, AH^= 1.8(3) kcal/mol and £«, = 9.3(9) eu. The treatment of CpCr(N0)2(N02) with Na15N02 in MeOH leads to the exchange of free and bound N02~, eventually giving a statistical distribution of the 15N label in the NO and N02 ligands and free N02" at equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Hubbard et al reported that formal isomerization of the nitrosyl complex, in which a nitro or nitrito ligand lies cis to the nitrosyl ligand, occurred via oxygen transfer from the nitrite ion to the nitrosyl ligand. 24 Although the isomerization from [1] ϩ to [2] ϩ can be explained by Hubbard's mechanism, that from [1] ϩ to [3] ϩ can not. In fact, experiments using 15 N-labeled compounds, Na Ϫ in H 2 O, which indicates that not only oxygen transfer but also nitrogen transfer occurs between the nitrosyl and the nitro ligand located cis to each other.…”
Section: Isomerization Reactionsmentioning
confidence: 99%
“…Hubbard et al reported that formal isomerization of the nitrosyl complex, in which a nitro or nitrito ligand lies cis to the nitrosyl ligand, occurred via oxygen transfer from the nitrite ion to the nitrosyl ligand. 24 Although the isomerization from [1] ϩ to [2] ϩ can be explained by Hubbard's mechanism, that from [1] ϩ to [3] ϩ can not. In fact, experiments using 15 N-labeled compounds, Na Ϫ in H 2 O, which indicates that not only oxygen transfer but also nitrogen transfer occurs between the nitrosyl and the nitro ligand located cis to each other.…”
Section: Isomerization Reactionsmentioning
confidence: 99%
“…After oxygen transfer, the remaining NO group can still exhibit nitrosyl-isonitrosyl isomerism. 16,[47][48][49][50][51][52] Kovalevsky and co-workers 53 showed, via crystallographic and IR analyses, that at low temperatures (90 K) intramolecular oxygen transfer occurs from the nitro to the nitrosyl group. At 200 K, only the isomer containing the nitrito ligand was observed (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of the reaction was explained by the kinetic inactivity and stability of the {RuNO} 6 species, compared with the iron complex. The thermally-induced oxygen transfer reaction occurs in crystals of [CpCr(NO) 2 [15] During the reaction the oxygen may either be transferred to the nitrosyl from the nitro isomer or from the nitrito isomer, which would be first thermally generated. In MeOH solution at 24 8C the ligands spontaneously inter-convert, similar to the iron complex.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Earlier we discussed the possibility of double linkage isomerization occurring on irradiation of [(tpp)Fe(NO)-(NO 2 )]. [23] The results were based on the solid state (KBr pellets) FT-IR data collected for the 15 N-isotopically labeled samples. No photocrystallographic experiments could be carried out due to the poor transparency of the porphyrin crystals to the laser light.…”
Section: Introductionmentioning
confidence: 99%